The Estonian Currency Board : Its Introduction and Role in the Early Success of Estonia's Transition to a Market Economy - Sutt, Andres; Knobl, Adalbert; Zavoiceo, Basil (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews the history of the introduction of the Estonian kroon under a currency board arrangement. On June 20, 1992, Estonia became the first country from the former Soviet Union to abandon the Russian ruble and introduce its own currency. The paper looks at the factors behind this decision and discusses the implementation of the currency reform. It then assesses the economic impact of the reform and also compares Estonia's experience with that of its Baltic neighbors. It concludes that although the currency board arrangement made an important contribution to the early success of Estonia's economic stabilization and reform program, the underlying financial and structural policies were crucial for that success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet